2009
DOI: 10.3390/su1041305
|View full text |Cite
|
Sign up to set email alerts
|

Economy and Sustainability—How Economic Integration Stimulates Stringent Environmental Regulations

Abstract: Abstract:The interaction between economic integration and environmental policy has become an important issue in the last few years. Despite the considerable scholarly attention this topic attracted, actual government responses in terms of environmental policy outputs remain largely untouched by both theoretical and empirical work. To fill this gap, we suggest a theory-based disaggregation of the compound variable economic integration for deriving more precise expectations on its differential impact on environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similarly, both Zhan et al 2014and Liu et al (2018) find that environmental protection in China is lacking because of the country's weak enforcement of rules and regulations. As such, scholars have suggested that improving existing regulatory frameworks and rule enforcement effectiveness are promising paths for stimulating sustainable development (de Abreu 2009;Tosun and Knill 2009). We expect a similar dynamic to apply in the context of CSP.…”
Section: Rule Of Lawmentioning
confidence: 81%
“…Similarly, both Zhan et al 2014and Liu et al (2018) find that environmental protection in China is lacking because of the country's weak enforcement of rules and regulations. As such, scholars have suggested that improving existing regulatory frameworks and rule enforcement effectiveness are promising paths for stimulating sustainable development (de Abreu 2009;Tosun and Knill 2009). We expect a similar dynamic to apply in the context of CSP.…”
Section: Rule Of Lawmentioning
confidence: 81%
“…The design of ERs is of crucial importance to examine the Porter Hypothesis. According to Majumdar and Tosun [29,30], ERs were divided into two types: flexible and inflexible. Flexible regulation characterized by little administrative control encourages industrial enterprises to develop appropriate processes to meet environmental standards, while inflexible regulation combines powerful administrative control with little incentive [5].…”
Section: Independent Variablementioning
confidence: 99%
“…Three types of the model are defined as follows: When δ = 0, Equation 13is an SDM model; when δ = 0, γ = 0, it is an SLM model; when σ = 0, η = 0, and δ = 0, it is an SEM model. [55] divided ERs into agile regulations and stiff regulations. Chris et al [56] divided ERs into voluntary regulations and mandatory regulations.…”
Section: Space Panel Econometric Modelsmentioning
confidence: 99%